Secondhand smoking exposure and quality of life among pregnant and postnatal women: a network approach. Issue 9 (16th September 2022) - Yang, Yuan; Zhang, Meng; Bo, Hai-Xin; Zhang, Dong-Ying; Ma, Liang-Kun; Wang, Pei-Hong; Liu, Xiao-Hua; Ge, Li-Na; Lin, Wen-Xuan; Xu, Yang; Zhang, Ya-Lan; Li, Feng-Juan; et al.
Abstract : Objective: This study examined the prevalence of exposure to secondhand smoke, its correlates and its association with quality of life (QOL) among pregnant and postnatal Chinese women. Design: This was a multicentre, cross-sectional study. Setting: Participants were consecutively recruited from eight tertiary hospitals located in eight municipalities or provinces in China. Participants: A total of 1140 women were invited to join this study and 992 (87.02%) completed all measures. Primary and secondary outcome: Measures women's secondhand smoking behaviour (frequency and location of exposure to secondhand smoking), and their QOL measured by the WHO Quality of Life Questionnaire. Results: A total of 211 women (21.3%, 95% CI 18.7% to 23.8%) had been exposed to secondhand smoking. Exposure to secondhand smoking was most common in public areas (56.4%), and residential homes (20.5%), while workplaces had the lowest rate of exposure (13.7%). Women with physical comorbidities were more likely to report secondhand smoking exposure, while older women, women living in urban areas, those with college or higher education level, and women in their second trimester were less likely to report exposure to secondhand smoking. Network analysis revealed that there were six significant links between secondhand smoke and QOL items. The strongest negative edge was the connection between secondhand smoke and QOL9 ('physical environment health', edge weight=−0.060), while the strongest positive edge was the connection between secondhand smoke and QOL3 ('pain and discomfort', edge weight=0.037). Conclusion: The prevalence of exposure to secondhand smoking is becoming lower among pregnant and postnatal women in China compared with findings reported in previous studies. Legal legislation should be maintained and promptly enforced to establish smoke-free environments in both public and private urban/rural areas for protection of pregnant and postnatal women, especially those who are physically vulnerable and less educated.